'He Brought the Cold Death on my Harandra': The Cosmic Trilogy and the Ecotheology of Laudato si'. (October 2018) - Johnson, Maria Poggi
Abstract : In his trilogy of space travel novels, published between 1938 and 1945, C.S. Lewis strikingly anticipates, and incarnates in imaginative form, the insights and concerns central to the modern discipline of ecotheology. The moral and spiritual battle that forms the plot of the novels is enacted and informed by the relationship between humans and the natural environment, Rebellion against, and alienation from, the Creator inevitably manifests in a violent and alienated attitude to creation, which is seen as something to be mastered and exploited. Lives and cultures in harmony with the divine will, on the other hand, are expressed in relationships of care and respect for the environment. The imaginative premise of the Trilogy is that of ecotheology; that the human relationships with God, neighbour, and earth and are deeply and inextricably intertwined.